2019
DOI: 10.3390/v11090776
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Autophagy and DNA Viruses

Abstract: Autophagy is a catabolic biological process in the body. By targeting exogenous microorganisms and aged intracellular proteins and organelles and sending them to the lysosome for phagocytosis and degradation, autophagy contributes to energy recycling. When cells are stimulated by exogenous pathogenic microorganisms such as viruses, activation or inhibition of autophagy is often triggered. As autophagy has antiviral effects, many viruses may escape and resist the process by encoding viral proteins. At the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 135 publications
0
15
0
3
Order By: Relevance
“…Among other types of selective autophagy, xenophagy specifically targets intracellular pathogens for their degradation and further integration into both innate and adaptive immune responses [21,[23][24][25][26]. Conversely, in response to this cell-protective autophagy, several different families of viruses, including coronavirus, have adapted by evolving a large variety of strategies to escape and/or to benefit via the inhibition and/or stimulation of autophagy at different stages of the process [23,[27][28][29]. Thus, the identification of these interaction points might bring the opportunity to disrupt the viral replication cycle at specific stages by targeting selected steps of autophagy.…”
Section: Autophagy Interplays With the Replication Cycles Of Multiplementioning
confidence: 99%
“…Among other types of selective autophagy, xenophagy specifically targets intracellular pathogens for their degradation and further integration into both innate and adaptive immune responses [21,[23][24][25][26]. Conversely, in response to this cell-protective autophagy, several different families of viruses, including coronavirus, have adapted by evolving a large variety of strategies to escape and/or to benefit via the inhibition and/or stimulation of autophagy at different stages of the process [23,[27][28][29]. Thus, the identification of these interaction points might bring the opportunity to disrupt the viral replication cycle at specific stages by targeting selected steps of autophagy.…”
Section: Autophagy Interplays With the Replication Cycles Of Multiplementioning
confidence: 99%
“…Autophagy is a catabolic biological process in the body, which has antiviral efficacy by targeting viruses and sending them to the lysosome for phagocytosis and degradation. At the same time, viruses can also use autophagy to enhance their own replication ( 76 ). However, little is known about the association between BmNPV and autophagy.…”
Section: Viral Immune Evasion Mechanismmentioning
confidence: 99%
“…V-cyclin and K1 have been found to promote autophagy by stimulating the AMPK pathway ( 328 , 329 ) ( Figure 6 ). On the other hand, vFLIP restricts the autophagic machinery by inhibiting ATG3 and LC3 proteins ( 330 ) ( Figure 6 ). Once viral latency is established, LANA plays a fundamental role in maintaining this phase through NF-kB activation ( 331 ).…”
Section: Human Herpesvirusmentioning
confidence: 99%
“…Granato et al observed viral particles inside autophagic vesicles in the cytoplasm of PEL cells in active replication, thus postulating that autophagy may also be related to viral transport ( 332 ). Finally, another protein linked to viral latency is STAT3 (signal transducer and activator of transcription 3), which remains active in a state of viral latency ( 330 ). In dendritic cells, KSHV infection induces STAT3 phosphorylation, promoting cell survival and viral latency.…”
Section: Human Herpesvirusmentioning
confidence: 99%